Metal Hydrides as Energy Storage for Concentrated Solar Thermal Applications - Javadian-Deylami, Seyd Payam (Curtin University, 2017)
Hydrogen storage properties of LiBH4 may be changed by interaction with other complex hydrides due to an intimate interaction between the respective alkaline metals and boron which facilitate a relatively larger hydrogen storage capacity. The cyclic stability of the following binary complex hydride systems LiBH4-Ca(BH4)2, LiBH4-NaBH4 and LiBH4-NaAlH4 shows significant reversibility and due to their relative high gravimetric H2 storage capacity and specific heat storage capacity, they may potentially act as heat storage materials.